Independent CRP-Commissioned External Evaluation of the CGIAR Research Program on Agriculture for Nutrition and Health (A4NH) - Compton, Julia; McLean, D.; Emmens, B.; Balagamwala, M. (International Food Policy Research Institute, 2015)
An independent CRP commissioned evaluation of A4NH was completed in September 2015. The evaluation was one of the five CRP commissioned evaluations requested by the CGIAR Fund Council, to assist and inform he planning and approval process for Phase II of the CRPs. To assist CRPs in this effort, IEA is providing quality assurance advice and support, as well as quality validation and review of processes and outputs. More information can be found here: https://cas.cgiar.org/evaluation/publications/crp-commissioned-reviews-and-evaluations-iea-quality-assurance-support